How Learning Happens Seminal Works in Educational Psychology and What They Mean in Practice - Kirschner, Paul A.; Hendrick, Carl (Routledge, 2024)
How Learning Happens introduces 32 giants of educational research and their findings on how we learn and what we need to know to learn effectively, efficiently, and enjoyably. Many of these works have inspired researchers and teachers all around the world and have left a mark on how we teach today. Now updated to include a new section on Memory and Cognition with five new chapters, this revised second edition explores a selection of the key works on learning and teaching, chosen from the fields of educational psychology and cognitive psychology. It offers a roadmap of the most important discoveries in the way learning happens, with each chapter examining a different work and explaining its significance before describing the research, its implications for practice, and how it can be used in the classroom -- including the key takeaways for teachers. Clearly divided into seven sections, the book covers: Memory and cognition How the brain works Prerequisites for learning How learning can be supported Teacher activities Learning in context Cautionary tales Written by two leading experts and illustrated by Oliver Caviglioli, this is essential reading for teachers wanting to fully engage with and understand educational research as well as undergraduate students in the fields of education, educational psychology and the learning sciences